Impact of Super Cyclone Amphan on Agriculture and Farmers' Adaptation Strategies in the Coastal Region of Bangladesh - Md. Jahangir Kabir; Md. Abdus Salam; Md. Imran Omar; Md. Abdur Rouf Sarkar; Mohammad Chhiddikur Rahman; Afroza Chowdhury; Md. Shajedur Rahaman; Limon Deb; S. M. M. H. Noman; Md. Abu Bakr Siddique (Bangladesh Rice Research Institute, 2020)
A super tropical cyclone named "Amphan" struck the Bangladesh coast on 22 May 2020, which caused widespread damage to rice and non-rice crops across 26 Districts. This study aims to (i) delineate the impact of Amphan on farming and livelihoods of coastal households; (ii) identify the farmers' coping and adaptation strategies to the cyclone; and (iii) delineate farmers' suggestions for increasing crops production and adaptive capacity. Fourteen villages of seven Upazilas of four most Amphan affected districts such as Satkhira, Khulna, Bagherhat and Patuakhali were selected for the study. Both the qualitative and quantitative data were collected through online interviews from 84 knowledgeable farmers and 25 expert personnel of the Department of Agriculture Extension (DAE) using a pre-tested semi-structured questionnaire. The results show that most boro rice in the coastal area escaped from the adverse consequences of Amphan as over 95% of total the crop of the region was harvested before struck the cyclone. Besides, The Aus area decreased in the range between 38-60% of the target area due mainly to (i) damage seedling in the nursery and (ii) stagnant water in the fields. Besides, the yield of the rice crop might lower in the range between 7-15% compared to last year Aus yield because of (i) delay transplanting due to cyclone and (ii) inadequate fertilizer application and weeding due to lack of money. Besides, T. Aman yield may decrease in the range between 10 – 18% as compared to the normal season because of (i) delay transplanting due to delay managing cash for hired in power tractor and labour, (ii) apply less fertilizers due to decrease income, and (iii) increase area of local cultivars as it needs less fertilizers. The major coping strategies of the households to smoothen consumption included (i) used food stocked at home, (ii) received reliefs in kinds, (iii) sold livestock and trees, (iv) caught wild fish from water-bodies, (v) temporary migrated for off/nonfarm works. Most households had access to foods because of the government's relief programs. The farming adaptation strategies included (i) raised Aus seedling of local and modern cultivars (ii) planted vegetables in the home-yard and dike of gher, and (iii) stocked shrimp and prawn post-larvae in the gher. Famers ability to invest in the farm decreased substantially due to (i) loss of farm income (BDT 50,000-130,000 per household) because of damage of crops and gone out shrimp and fish from ghers, and (ii) decreased off/non-farm incomes (BDT 18,000-26,000 per household) due to the outbreak of COVID-19. The government helped farmers by reducing T. Aman rice seed prices (BDT 10/kg). Due to lack of resources, DAE provided limited material supports to Amphan affected farmers in the Aman rice. Farmers and experts suggested following interventions to minimize the impact of Amphan cyclone to farmers: (i) ensuring easy access to bank credit at a low-interest rate, (ii) providing inputs and cash supports to small and marginal farmers (iii) reduced fertilizer price by 50% for Amphan affected areas to ensure a better harvest of T. Aman. Furthermore, farmers suggested for (i) re-excavation of the canals for better access to fresh-water for irrigation, (ii) raising 2-3 feet elevation of the Embankments, (iii) placing the RCC block on the Embankment for protecting the breakage by the tidal surge, (iv) repairing the old sluice gates and set some new sluice gates for protecting salinity intrusion and drainage out stagnant water, and (v) ensuring access to market and fair price of rice and non-rice crops, shrimp and fish for sustainable farm production.
Keywords: 330; Amphan; COVID-19; Yield loss; Climate change; Adaptation; Coastal